Analysis Of Junior High School Students' Mathematical Creative Thinking Ability Reviewed By Gender - Annisa, Syifa; Fitriani, Nelly; Amelia, Risma ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
This research is motivated by the importance of creative mathematical thinking skills for students studying mathematics. This study aims to analyze students' mathematical creative thinking skills in terms of gender. This study used a qualitative descriptive method. The population in this study was 20 grade IX students of SMP Negeri 2 Cimahi who were used as a sample, consisting of 10 male students and 10 female students who were randomly selected. The instrument used in this study is to provide four mathematical creative thinking questions consisting of indicators of fluency, flexibility, originality, and elaboration. The data in this study were analyzed using the value of the percentage of students who had done mathematical creative thinking problems that had been given and then compared based on gender. The results of the research that has been conducted revealed that overall, the ability of female students to think creatively mathematically is valued higher than the ability of male students to think creatively mathematically. This can be seen in terms of the proportion of overall value or certain aspects. Regarding fluency, male students score higher than female students, while female students score higher on flexibility, originality, and elaboration. It can be concluded that gender can affect students' ability to creative mathematical thinking skills.